Od kompetencí k obsahům | From competences to content - Karel Šebesta; Tora Hedin (Studie z Aplikované Lingvistiky, 2019)
The authors consider how the relationship between reading literacy and communication education can be defined and using the example of education for critical reading, they present communication education as an autonomous component of the Czech language and literature education, with its own subject matter, educational objectives and content. They gradually come to the realisation that reading literacy, as it is usually understood, belongs among key competences due to its character (it is part of the communication competence). Supported by the results of the analyses of the causes of curricular reform failure, they draw attention to the potential risks which may arise when we attempt to translate key competences directly into teaching. They claim that it is essential to start from a sectoral basis, to formulate field-specific educational objectives and content in individual fields of education and to investigate their relation to key competencies. In the final part of their reflection, they present a model of communication education which deals with mental processes and structures associated with communication activities, while the educational goal then lies in the students’ ability to reflect on these processes and influence them in accordance with their own needs and intentions. In this concept, educational content is the theory, terminology and knowledge needed to understand these processes.